Estimativa da demanda hídrica potencial na irrigação por pivô central na bacia do Rio Urucuia utilizando índice de vegetação NDVI - Souza, Bruno de Oliveira (2016)
This study was developed with the objective of estimating the evapotranspiration, as well as the hydric demand of irrigated crops by center pivots in the Urucuia River’s basin, in the year of 2013, using temporal series of MODIS products and field data collected in the weather station of Arinos-MG. Altogether, 344 center pivots were mapped in the basin, with a total area of 30,3032 ha. Unaí was the county that had the highest concentration of center pivots (31.4%), the county also recorded the highest hydric demand of the entire basin. The temporal profiles of NDVI allowed the analysis of the cycle of agricultural crops throughout the months of the year, with the aid of temporal series of EVI2 was possible to identify which agricultural crop was implanted under determinate center pivot. Estimated from an application efficiency of 100%, the hydric demand of the irrigated areas by center pivots represented 18.9% of Q7,10. Considered an application efficiency of 90%, this valor corresponded to 20.9% of Q7,10. Lastly, considering the lowest application efficiency allowed (60%), the hydric demand reached 31.4% of Q7,10, a disturbing number, once it surpasses the 30% allowed. Considering the results gotten, it is concluded that the use of water for irrigation in the studied basin is above the recommended, indicating the need of the reassessment of the use of water intended to irrigated agriculture in the region.